Oxygen Diffusion into Multiwalled Carbon Nanotube Doped Polystrene Latex Films Using Fluorescence Technique - Yargi, Onder; Ugur, Saziye; Pekcan, Onder (SPRINGER/PLENUM PUBLISHERS, 2013)
This study examines the oxygen diffusion into polystyrene (PS) latex/multiwalled carbon nanotube (MWNT) nanocomposite films (PS/MWNT) consisting of various amounts of MWNT via steady state fluorescence technique (SSF). PS/MWNT films were prepared from the mixture of MWNT and pyrene (P)-labeled PS latexes at various compositions at room temperature. These films were then annealed at 170 A degrees C above glass transition (T-g) temperature of PS. Fluorescence quenching measurements were performed for each film separately to evaluate the effect of MWNT content on oxygen diffusion. The Stern-Volmer equation for fluorescence quenching is combined with Fick's law for diffusion to derive the mathematical expressions. Diffusion coefficients (D) were produced and found to be increased from 1.1 x 10(-12) to 41 x 10(-12) cm(2)s(-1) with increasing MWNT content. This increase was explained via the existence of large amounts of pores in composite films which facilitate oxygen penetration into the structure.
Keywords: Carbon nanotubes; Fluorescence; Diffusion; Oxygen; Quenching; Composite film; TRANSPORT-PROPERTIES; LAYERED SILICATE; ORGANIC VAPORS; NANOCOMPOSITES; GASES; Biochemistry & Molecular Biology; Chemistry